PENGARUH GAME ONLINE TERHADAP TINGKAT KEMALASAN ANAK BELAJAR PADA ANAK USIA 7 – 12 TAHUN - Sariwardani, Andriani (Journal of Professional Elementary Education, 2024)
Children are more interested in playing online games available on the device. It can be very interesting for a child. However, not many people have the ability to choose games that are appropriate for their age, leading to negative attitudes and behaviors caused by online gaming it self. This research is a type of quantitative research with a cross-sectional approach used to examine independent and dependent variable data simultaneously with the aim of identifying the relationship between the two variables. This research used 84 respondents. Data collection was carried out using primary data, namely data obtained directly from respondents through interviews and filling out questionnaires. The analyses used are univariate and bivariate. Based on statistical tests, with a p value of 0.03, α = 0.05 compared to p < α, it can be concluded that there is a significant influence of online games on the level of laziness of children aged 7-12 years